Stability of hydrate-bearing sediment during methane hydrate production by depressurization or intermittent CO2/N2 injection. (15th April 2023) - Zhu, Yi-Jian; Chu, Yan-Song; Huang, Xing; Wang, Ling-Ban; Wang, Xiao-Hui; Xiao, Peng; Sun, Yi-Fei; Pang, Wei-Xin; Li, Qing-Ping; Sun, Chang-Yu; Chen, Guang-Jin
Abstract: Ensuring reservoir stability during natural gas hydrates production is the key to balance the geology-engineering-environment nexus. Under the overlying stress of 10 MPa, a series of experiments were conducted to investigate the variations of P-wave velocity, subsidence, and stratum stiffness during hydrate depressurization mining. The influence of hydrate saturations, gas production pressure, and sediment type were examined. The stratum stiffness of hydrate-bearing sediment gradually decreased with the decomposition of hydrate, despite the continuous compaction of overlying stress. Higher hydrate saturation led to larger subsidence and slower sedimentation rate. Lower gas production pressure resulted in greater subsidence and faster sedimentation rate. In sandy sediments, a larger particle size generated a larger sedimentation rate due to the strong heterogeneity of hydrate. However, the subsidence of silty clay is smaller with slower sedimentation rate. Hence, a novel method of intermittent CO2 /N2 injection below the freezing point was proposed, which kept the stratum stiffness, reduced the sedimentation rate and subsidence of the reservoir, but also realized the sequestration of CO2 simultaneously. The method greatly enhanced the recovery ratio of methane hydrate below the freezing point. These findings provide guidance for the safe and efficient exploitation of natural gas hydrate in future. Highlights: The stratum stiffness of hydrate-bearing sediment decreases with the decomposition of hydrate. Higher hydrate saturation leads to larger subsidence and slower sedimentation rate. Lower gas production pressure leads to greater subsidence and faster sedimentation rate. A larger sediment particle size leads to a larger sedimentation rate. Intermittent CO2 /N2 injection below 0 °C favors the stability of hydrate-bearing sediment.